Russian Economic Report, September 2015 : Balancing Economic Adjustment and Transformation - World Bank Group (World Bank, Washington, DC, 2015)
Russia’s recession deepened in the first half of 2015 with a severe impact on households. The economy continues to adjust to the 2014 terms-of-trade shock amid a tense geopolitical context marked by ongoing international sanctions. Oil and gas prices remained low through the first half of 2015, further underscoring Russia’s vulnerability to volatile global commodity markets. The weakening of the ruble created a price advantage for some industries, boosting a narrow range of exports and encouraging investment in a certain sectors, but this was not sufficient to generate an overall increase in non-energy exports. Investment demand continued to contract for a third consecutive year. Economic policy uncertainty arising from an unpredictable geopolitical situation and the continuation of the sanctions regime caused private investment to decline rapidly as capital costs rose and consumer demand evaporated. The record drop in consumer demand was driven by a sharp contraction in real wages, which fell by an average of 8.5 percent in the first six months of 2015, illustrating the severity of the recession. However, the deterioration of real wages was also the primary mechanism through which the labor market adjusted to lower demand, and unemployment increased only slightly from 5.3 percent in 2014 to 5.6 percent in the first half of 2015. The erosion of real income significantly increased the poverty rate and exacerbated the vulnerability of households in the lower 40 percent of the income distribution.